The Accounting Conservatism and Its Effect on the Quality of Financial Reporting and Supply Chain of Organization in the Financial Market - Fadhil Shaalan Jabbar (International Journal of Supply Chain Management, 2019)
Accounting conservatism is one of the well-established accounting policies that is used in the field of accounting. In the past, it has been highly praised because conservatism increases the credibility and reliability of financial statements and helps to protect the stakeholders. The sound application of accounting conservatism leads to improve the quality of financial reporting through confessing and disclosing, in the appropriate time, the unwanted news that might face the company. But the company management can have an influence on practicing financial conservatism by intervening in the measurement and disclosure processes of the company results and its financial position, which aims to mislead financial statements users. Although accounting conservatism has been criticized severely due to its contradiction with certain qualitative standards of accounting information, it does not attract local (Iraqi) attention in which it has an important role to enhance financial reporting in the Iraqi environment. Because Iraq tries to attract foreign companies to work and invest in the country, which requires to provide sufficient information to helps them take sound decisions. The study aims to shed light on the relationship between accounting conservatism and the improvement of the quality of financial statements, and the effect of this relationship on the supply chain of the organization in the financial market. Conservatism can be used by the company management as a way of accounting alternatives in an opportunistic and practical way through some accounting policies that the companies apply. In order to reach the study goals, the necessary data and information have been gathered to test the study hypotheses. The study achieves statistically important indicators about the level of accounting conservatism in the financial statements issued by the joint- stock companies in Iraq stock exchange.